Central Venous Catheter-Related Tachycardia in the Newborn: Case Report and Literature Review - Aya Amer; Roland S. Broadbent; Liza Edmonds; Benjamin J. Wheeler (Case Reports in Medicine)
Central venous access is an important aspect of neonatal intensive care management. Malpositioned central catheters have been reported to induce cardiac tachyarrhythmia in adult populations and there are case reports within the neonatal population. We present a case of a preterm neonate with a preexisting umbilical venous catheter (UVC), who then developed a supraventricular tachycardia (SVT). This was initially treated with intravenous adenosine with transient reversion. Catheter migration was subsequently detected, with the UVC tip located within the heart. Upon withdrawal of the UVC and a final dose of adenosine, the arrhythmia permanently resolved. Our literature review confirms that tachyarrhythmia is a rare but recognised neonatal complication of malpositioned central venous catheters. We recommend the immediate investigation of central catheter position when managing neonatal tachyarrhythmia, as catheter repositioning is an essential aspect of management.